A hely szelleme: A debreceniség szociológiai szempontú vizsgálata a helyi kulturális eliten belül - Béres, Zsuzsa (Studia Litteraria, 2021)
Considering the cultural elite of Debrecen, it is inevitable to interpret the social and cultural phenomenon, which is known as the identity of Debrecen and appears in the public consciousness. The concept of the identity of Debrecen is still incomplete in the social sciences, only literary science researched this concept. In my study I try to understand what constructs nowadays the identity of Debrecen, the concept: ’debreceniség’. To understand this concept I use my empirical results, in which I asked the cultural elite in Debrecen, what they think about ’debreceniség’. The results are dichotomous, but the community recognises this concept, and some people can fill it with content, too.